Diurnal variation of zooplankton biochemical composition and biomass in plankton production tanks - Santeiro, Rachel Magalhães [UNESP]; Pinto-Coelho, Ricardo Motta; Sipaúba-Tavares, Lúcia Helena [UNESP] (Universidade Estadual de Maringa, 2006)
The nutritional value of zooplankton (lipid and phosphorus contents) was analyzed in outdoor, plankton-culture tanks, to monitor the effects of diurnal variation and fertilization. Total lipid contents were significantly higher (average values of about 14% DW) for the treatment fertilized during the sampling week. A significantly highher total lipid concentrations generally coincided with high biomass of Moina sp. (Cladocera) and Thermocyclops sp. nauplii (Copepoda), which is probably related to zooplankton filtration rates. The values tended to be higher during the afternoon and the night. Phosphorus contents in the zooplanktonic population varied from 0.15 to 0.91% DW, with significant differences among the tanks. The zooplankton nutritional quality was greatly influenced by fertilization, which also determined the species composition in the tanks.
Keywords: Biochemical composition; Biomass; Plankton tanks; Zooplankton; aquatic environment; biochemical composition; biomass; biomass production; circadian rhythm; Cladocera; copepod; human; nutrition; zooplankton; Copepoda; Moina; Thermocyclops